1993
DOI: 10.1111/j.1365-2621.1993.tb03233.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Growth and Volatile Compounds in Yoghurt‐Type Products from Soymilk ContainingBifidobacterium ssp

Abstract: The growth of bacteria normally used to produce yoghurt was compared in soymilk and cow milk. Whether or not Bifidobnc&ium ssp. was present, fermented soymilks [soyoghurt (S), soyoghurt f bifidobacteria (SB)] were less acidic than fermented cow milks [yoghurt (Y), yoghurt + bifidobacteria (YB)]. When bifidobacteria were present (in SB), streptococci were more numerous than lactobacilli. Bifidobacteria in YB stimulated maximal growth of both yoghurt bacteria. In comparison to nonfermented milks, acetaldehyde an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 36 publications
6
44
0
1
Order By: Relevance
“…1a and 1b). MURTI et al (1992) reported that in mixed cultures containing lactobacilli and bifidobacteria, the former one exhibited faster growth than the latter one resulting in higher cell numbers. On the other hand, a good balance of these species is desirable in fermented beverages since both may be related with health-promoting effects (KLAVER et al 1993).…”
Section: Ratio Of L Casei Ssp Shirota and B Adolescentis In The Inmentioning
confidence: 98%
“…1a and 1b). MURTI et al (1992) reported that in mixed cultures containing lactobacilli and bifidobacteria, the former one exhibited faster growth than the latter one resulting in higher cell numbers. On the other hand, a good balance of these species is desirable in fermented beverages since both may be related with health-promoting effects (KLAVER et al 1993).…”
Section: Ratio Of L Casei Ssp Shirota and B Adolescentis In The Inmentioning
confidence: 98%
“…Bifidobacterium spp. can reduce the off-flavor of n-hexanal [30,32] and ferment sucrose, raffinose and stachyose [7]. Furthermore, a significantly higher reduction in raffinose and stachyose content was found in soymilk fermented with mixed cultures of bifidobacteria and lactic acid bacteria than in those fermented with single lactic acid bacterium culture [36].…”
Section: Introductionmentioning
confidence: 94%
“…Soymilk based fermented food i.e. soy curd may provide additional benefit for the consumer due to their hypolipidemis (Trindade 2001), anticholesterolemic, antiatherogenic properties and reduced allergenicity (Murti 2006). Consequently soymilk based yogurt offers a considerable appeal to a growing segment of consumers with certain dietary and health concerns (Messina et al 1994;Lui 1997).…”
mentioning
confidence: 99%